Telaah Diksi Agama dalam Kamus Al-Munjid Fi Al-Lughah Wa Al-A'lam - Muhammad Subhan (DINAMIKA : Jurnal Kajian Pendidikan dan Keislaman, 2023)
Al-Munjid's dictionary is often used by the majority of Muslims in the world because it is considered easy in vocabulary entry and search. However, there is still much debate about its use because the vocabulary is considered to influence the faith of a Muslim. Some scholars consider al-Munjid's dictionary to have links with the orientalist movement, which carries a hidden agenda toward the Islamic world. So the purpose of this study is to criticize and examine diction related to religious tendencies towards the concept of al-Munjid's dictionary and see the accuracy of the interpretation or meaning given by looking at "diction" in Al-Munjid. The research was conducted by listening to the diction and language styles contained in the Al-Munjid Fi al-Lughah Wa al-A'lam dictionary, then providing data followed by note-taking techniques, namely recording data used as the object of research then the data was analyzed using an equivalent method. The study results explain that according to some Ulama, the al-Munjid Fi al-Lughah Wa al-A'lam Dictionary has advantages and disadvantages, which creates a tendency for religious sensitivity to dictionary concepts. A noticeable deviation is found in al-Munjid's dictionary and then demanded that Shaykh Masyhur Hasan Salman, a grand mufti, issue a fatwa leaving the dictionary as a reference and even a reference because the religious diction towards Islam was very incompatible, so in studying Islamic sciences and taking alternative dictionaries -another dictionary that is much more complete and original.